2010
DOI: 10.4261/1305-3825.dir.3437-10.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevelance of aortic root dilation in patients with cta of the aorta

Abstract: 272T horacic aortic aneurysm (TAA) is a potentially life-threatening disorder if not diagnosed before the development of dissection and rupture. TAA is defined as a localized dilation of the aorta to more than 50% of baseline. The incidence of TAA is estimated at 6 people per 100,000 per year, and the mean age at diagnosis is 60-70 years. (1). Of all patients presenting with TAA, 60% involve the aortic root and/or ascending aorta (2). The aortic root is described as the part of the aorta that supports the aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In previous studies, the size, number, and form variations of TFs were observed and morphometric measurements were done on dry cadaveric materials (2)(3)(4)(5)(6). In the previous studies, it was reported that multidetector computed tomography (MDCT) with 3-dimensional (3D) volume rendering (VR), multiplanar reconstruction (MPR), and maximum intensity projection (MIP) techniques has a very high sensitivity in evaluating anatomic (bony and vascular) variations and anatomic localization (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). To the best of our knowledge, this is the first study in the literature that evaluates the variations of TFs by MDCT.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the size, number, and form variations of TFs were observed and morphometric measurements were done on dry cadaveric materials (2)(3)(4)(5)(6). In the previous studies, it was reported that multidetector computed tomography (MDCT) with 3-dimensional (3D) volume rendering (VR), multiplanar reconstruction (MPR), and maximum intensity projection (MIP) techniques has a very high sensitivity in evaluating anatomic (bony and vascular) variations and anatomic localization (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). To the best of our knowledge, this is the first study in the literature that evaluates the variations of TFs by MDCT.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with massive aortic aneurysms encompassing the coronary artery ostia can be evaluated with MDCT-CA (Fig. 11) (46). Performing catheter angiography in these patients is very difficult because the widened lumen makes it almost impossible to locate the ostium with the catheter.…”
Section: Conditions In Which Access To Coronary Ostia Is Challengingmentioning
confidence: 99%